ANALISIS EVALUASI PROGRAM PEMBANGUNAN JANGKA MENENGAH DAERAH BIDANG PENDIDIKAN DI KABUPATEN KUTAI BARAT TAHUN 2011-2015 - Marelis Suhud Gustaf (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This article aim to describe and evaluate the Program Medium Term Development of Education in West Kutai. The results showed that the medium-term development program in education in West Kutai in terms of the effectiveness of that activity carried out effectively enough for the planned program had been implemented and completed. Viewed from in terms of efficiency that the programs implemented are not efficient because it uses a substantial budget.Keyword : Evaluation, Program of Education, West Kutai